The effect of booster breaks on non-specific low back pain in office workers - Uršič, Tajda; Marušič, Uroš (Annales Kinesiologiae, 2025)
Purpose: Prolonged sitting has a negative effect on office workers, and non-specific low back pain (NSLBP) is one of the most common consequences of an inactive lifestyle and prolonged sitting. Active breaks are a promising intervention to reduce the negative effects of office work. Methods: Forty-two office workers from a Slovenian company were divided into an experimental group (24 office workers who had been taking active breaks for one and a half years) and a control group (N=18, no active breaks). The participants were not randomly allocated to the groups; allocation was based on availability and voluntary participation. An online survey was conducted using the Oswestry Disability Index 2.0 (ODI 2.0) and the Visual Analog Scale (VAS). This was a non-randomized, two-arm longitudinal study. Questionnaires were administered once, 1.5 years after the intervention. Statistical analyses were conducted using the Mann-Whitney and Wilcoxon signed-rank tests, with the level of significance set at p ≤ 0.05. Results: The results showed that 81% of office workers had experienced NSLBP at least once in their lives. The ODI 2.0 scores were not significantly lower in the experimental group (p = 0.155). However, pain intensity was lower in office workers who took active breaks (p = 0.001). All the participants in the experimental group reported that active breaks had a positive effect on their well-being (100%). Furthermore, 37.5% of the participants stated that they had become more physically active outside the office as a result of the active breaks. Conclusion: Introducing active breaks into the daily routine of office workers is a viable and effective intervention to mitigate the risk of NSLBP. Active breaks offer a comprehensive solution: they not only reduce the negative effects of prolonged sitting, but also reduce stress, improve work efficiency and focus, and promote better moods.